Improving firm survival: exports or outward foreign direct investment? - Dai, Meihong; Li, Ben (Post-Communist Economies, 2020)
Firm survival matters not only for the development of firms, but also for industrial development and macro-economic growth. This paper aims to explore a far less studied issue: the impact of exports and outward foreign direct investment (OFDI) on firm survival. First, this research explores the impact of pure-exports, pure-OFDI and mixed trade on firm survival based on a heterogeneous firm model with dynamic conditions. Second, this research demonstrates the theoretical hypothesis by employing micro-data from China and the multiple propensity score matching method. The results indicate that both exports and OFDI help improve firm survival, though the impact of pure-OFDI is larger. This conclusion is robust across different matching algorithms, research periods and empirical methods. The heterogeneous analysis indicates that the 'exports/OFDI–firm survival' relationship varies across both firm and economic characteristics. This research aims to guide firms' optimal method of internationalisation and provide suggestions for the development of a new opening-up pattern.